In-situ observation of nanoscale transformations in dehydrating lizardite - Mutian Qin; Huilin Xing; Jianchao Wang; Guodong Jin; Zhongwen Hu; Weichao Yan; Yuyang Tan; Junbiao Liu; Rongxin Zhang (Scientific Reports)
Abstract Dehydration of serpentine is an important prograde metamorphic reaction within the lithosphere and subduction zones, potentially causing profound changes in rock properties. Imaging these transitions in real time provides direct insight into the process. We have used in-situ transmission electron microscopy (TEM) to continuously monitor nanoscale transformations in lizardite from 20 to 600 °C. Phase transformation processes during dehydration are recorded and analyzed in real time, including the amorphization of lizardite, and the recrystallization of nanocrystalline forsterite and talc within amorphous dehydroxylate phases. These observations delimitate the role of dehydration temperature in controlling reaction kinetics and the nucleation of reaction products. Specifically, the higher the temperature, the faster the rate of lizardite dehydration, accompanied by faster and more extensive nucleation of nanocrystalline forsterite and talc. Furthermore, the lizardite crystal is observed to gradually shrink with dehydration while maintaining its structural integrity, leading to the expansion of nanoscale intergranular pores and the formation of interconnected pore networks.